Assessing k‑Point Mesh Density for Accurate DFT Modeling (1x1) unit cell of Graphene - Ghaniya, Ega Abdillah; Akmal, Daffa Hadyan; Zulbadri, Muhammad Dzaki Adlil; Putra, Septia Eka Marsha (Greensusmater, 2025)
This study systematically evaluated the influence of k-points mesh density and offset conditions on the structural accuracy, total energy convergence, and computational efficiency of a pristine graphene system. The total energy results indicate that convergence is achieved at a k-points mesh of 12×12×1, with negligible variations up to 20×20×1. Similarly, structural parameters, including lattice constants and C–C bond lengths, demonstrate minimal deviation at higher mesh densities. However, computational time increases non-linearly with k-points density, especially under offset conditions, highlighting the trade-off between precision and computational cost. Based on a comprehensive assessment of energy stability, structural consistency, and time efficiency, the 16×16×1 no-offset k-points mesh emerges as the most balanced and reliable configuration. It yields the lowest total energy, exhibits excellent agreement with established structural benchmarks, and avoids excessive computational demand. This makes it particularly suitable as a reference system for future ab initio studies, such as H₂O adsorption on graphene, where accurate baseline energies are critical for computing adsorption energetics. The findings underscore the importance of k-points convergence testing in density functional theory (DFT) simulations and support prior literature emphasizing the balance between computational accuracy and efficiency. Future adsorption studies can confidently adopt the identified k-points mesh to ensure both reliable results and computational feasibility.